The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.nlm.2008.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic activation of the basolateral amygdala modulates consolidation of object recognition memory

Abstract: Noradrenergic activation of the basolateral complex of the amygdala (BLA) modulates the consolidation of memory for many kinds of highly emotionally arousing training tasks. The present experiments investigated whether posttraining noradrenergic activation of the BLA is sufficient to enable memory consolidation of a low-arousing training experience. Sprague-Dawley rats received intra-BLA infusions of norepinephrine, the β-adrenoceptor antagonist propranolol or saline immediately after either 3 or 10 min of obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
162
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(182 citation statements)
references
References 25 publications
20
162
0
Order By: Relevance
“…Prior studies indicate that the BLA modulates the consolidation for many different types of learning including inhibitory avoidance (LaLumiere et al 2004(LaLumiere et al , 2005, CFC Huff and Rudy 2004), conditioned taste aversion (Miranda et al 2003;Guzman-Ramos and Bermudez-Rattoni 2012), spatial and cued-response learning (Packard et al 1994), and novel object recognition (Roozendaal et al 2008;Bass et al 2012). However, evidence also indicates that different types or kinds of learning involve separate and distinct brain regions, as, for example, the hippocampus and caudate are involved in the consolidation of spatial and cued water maze learning, respectively (Packard et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies indicate that the BLA modulates the consolidation for many different types of learning including inhibitory avoidance (LaLumiere et al 2004(LaLumiere et al , 2005, CFC Huff and Rudy 2004), conditioned taste aversion (Miranda et al 2003;Guzman-Ramos and Bermudez-Rattoni 2012), spatial and cued-response learning (Packard et al 1994), and novel object recognition (Roozendaal et al 2008;Bass et al 2012). However, evidence also indicates that different types or kinds of learning involve separate and distinct brain regions, as, for example, the hippocampus and caudate are involved in the consolidation of spatial and cued water maze learning, respectively (Packard et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, all discrimination measures of the 3 rd familiarization session were higher compared to any of other individual sessions except the 4 th . Many studies have shown that stress can have varying effects on memory functioning [50][51][52][53][54][55]. Memory can be facilitated when stress is experienced in the same context and around the time of learning [56].…”
Section: Familiarizationmentioning
confidence: 99%
“…Along these lines, while hippocampal lesions have been shown to significantly impair object recognition (Broadbent et al 2010), cortical regions such as the perirhinal and medial prefrontal cortex are also implicated in object recognition (Barker and Warburton 2011), as is the basolateral amygdala (Roozendaal et al 2008). Hence, the involvement of MSK1 in these brain regions cannot be excluded as a contributing factor to the observed object recognition memory deficits.…”
Section: Msk Learning and Memorymentioning
confidence: 99%